Managing diabetes : the cultural politics of disease - Bennett, Jeffrey A. (Jeffrey Allen), 1974- (Biopolitics (New York, N.Y.), 2019)
A critical study of diabetes in the popular imagination Over twenty-nine million people in the United States, more than nine percent of the population, have some form of diabetes. In Managing Diabetes, Jeffrey A. Bennett focuses on how the disease is imagined in public culture. Bennett argues that popular anecdotes, media representation, and communal myths are as meaningful as medical and scientific understandings of the disease. In focusing on the public character of the disease, Bennett looks at health campaigns and promotions as well as the debate over public figures like Sonia Sotomayor and her management of type 1 diabetes. Bennett examines the confusing and contradictory public depictions of diabetes to demonstrate how management of the disease is not only clinical but also cultural. Bennett also has type 1 diabetes and speaks from personal experience about the many misunderstandings and myths that are alive in the popular imagination. Ultimately, Managing Diabetes offers a fresh take on how disease is understood in contemporary society and the ways that stigma, fatalism, and health can intersect to shape diabetes's public character. This disease has dire health implications, and rates keep rising. Bennett argues that until it is better understood it cannot be better treated